Strategic customer management: sales is a strategic issue - Piercy, Nigel (Henry Stewart Talks, 2010)
Putting sales back on the boardroom agenda, Sales may be the only place you can add value, The changing sales force role, Forces driving the sales organization, Evolution in business functions, Imperatives for the strategic sales organization, Leadership in strategy, Screening the customer portfolio, Intelligence and market sensing capabilities, Integration and value processes, Internal marketing, Sales organization infrastructure, Inspiration and the leadership gap, Influence to lead change, Integrity and customer value, International sales management issues, Managing the transformation, Is sales the new marketing?